Community Participation in the Development Plan of Mande Village, Mande District, Cianjur Regency - Hesti Geovany, Dede; Rachmawati, Ike; Hegia Sampurna, Rizky (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2025)
This study aims to analyze community participation in the Village Development Planning Conference (Musrenbangdes) in Mande Village, Mande District, Cianjur Regency. The research uses qualitative methods with data collection techniques in the form of observation, interviews, and documentation, as well as data analysis of the Miles and Huberman interactive model. The results of the study show that community participation in Musrenbangdes includes four dimensions: decision-making, planning, utilization of results, and evaluation. Despite the active involvement of the community in the decision-making process through hamlet-level deliberations (Musdus) and supervision by the Village Consultative Body (BPD), the level of community attendance and contribution in providing input is still low, with an average attendance of only 19% of the number of invitees. The main challenges include budget limitations, lack of public awareness, and the perception that Musrenbang is only a formality. Nevertheless, several priority programs, such as the construction of the Sports Building (GOR), road repairs, and the construction of drilled wells, have had a positive impact on the quality of life and the economy of the community. This study emphasizes the importance of intensive socialization, budget transparency, and an inclusive approach to increase community participation in village development. In conclusion, Musrenbangdes in Mande Village is able to encourage sustainable development, but it needs improvements in terms of participation and resource management to achieve more optimal results.